The study of efficacy and safety of expectant management of incomplete abortion - Kayastha, Sanita; Mainali, Sumina; Sah, Limu Kumari (Nepal Medical College Journal, 2022)
Expectant management of incomplete abortion is a watch full waiting without intervention for certain period of time so that the retained product of conception will be expelled spontaneously. This study was carried out to see feasibility and safety of expectant management of incomplete abortion. It was observational descriptive study which was carried out in Nepal Medical College Teaching Hospital from July to December 2020 in 60 patients of spontaneous incomplete abortion. The patients which fulfill the inclusion criteria were sent home after bleeding has settled and ultrasound was carried after two weeks to see the success of the treatment. The success of the expectant management was found in 86.7%. There were heavy bleeding in 6.7% cases, unscheduled surgical evacuation was done in 13.3% cases. Blood transfusion was carried out in 5.0% of cases. The number of cases complained of severe low abdomen pain were 8.3% and limitation of activity were present in 10.0% of cases. There was one (1.7%) patient who showed the sign of genital infection. With the success of 86.7% of expectant management of incomplete abortion in our study we can consider expectant management of incomplete abortion as a safe option. However, small percentage of complications such as heavy bleeding, emergency surgical evacuation and severe pain are seen.